Withanolide Profile and Acetylcholinesterase Inhibitory Activity of Two Argentinean Jaborosa Species - Alza, Natalia P.; Pferschy-Wenzig, Eva M.; Kunert, Olaf; Murray, Ana P. (Planta Medica, 2024)
Acetylcholinesterase (AChE) inhibitors are still an important option for managing symptoms of mild to moderate Alzheimerʼs disease. In this study, we aimed to evaluate the potential in vitro AChE inhibitory activity of two Argentinian endemic Solanaceae species, Jaborosa bergii and J. runcinata. UHPLC-DAD-HRMS metabolite profiling revealed the presence of withanolides in the active CH2Cl2 subextracts. Their fractionation led to the isolation and identification of two known spiranoid withanolides from J. runcinata and three new withanolides with a skeleton similar to that of trechonolide-type withanolides from J. bergii. The known compounds showed moderate AChE inhibitory activity, while the new ones were inactive.
Keywords: Withanolides; Jaborosa bergii; Jaborosa runcinata; Solanaceae; Alzheimerʼs disease; cholinesterase inhibition